2022
DOI: 10.9778/cmajo.20210238
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous leishmaniasis in travellers and migrants: a 10-year case series in a Canadian reference centre for tropical diseases

Abstract: Cutaneous and mucosal leishmaniasis are protozoan infections transmitted by the bite of female sandflies. This tropical disease affects 700 000 to 1 million new individuals annually. 1 Close to 20 species of Leishmania, belonging to 2 main subgenera (Leishmania and Viannia), are involved in human leishmaniasis. Cases of cutaneous leishmaniasis mainly occur in the Americas (New World leishmaniasis), as well as in the Mediterranean basin, the Middle East and Central Asia (Old World leishmaniasis).The clinical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Although the dose of IV L‐AmB used in CL is still controversial, administration of 3 mg/kg per day for 5 consecutive days and 6 doses on the 10th day, with a total cumulative dose not exceeding 18 mg/kg, was found to be effective 1,24 . However, different efficacy rates were also found in 15–32.5 mg/kg total dose applications 9,10,12–14,25–28 . (Table 2) In our study, we applied IV L‐AmB treatment as 3 mg/kg for 5 consecutive days and on the 10th day, in a total of 6 doses (18 mg/kg total dose).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Although the dose of IV L‐AmB used in CL is still controversial, administration of 3 mg/kg per day for 5 consecutive days and 6 doses on the 10th day, with a total cumulative dose not exceeding 18 mg/kg, was found to be effective 1,24 . However, different efficacy rates were also found in 15–32.5 mg/kg total dose applications 9,10,12–14,25–28 . (Table 2) In our study, we applied IV L‐AmB treatment as 3 mg/kg for 5 consecutive days and on the 10th day, in a total of 6 doses (18 mg/kg total dose).…”
Section: Discussionmentioning
confidence: 69%
“…When patients with delayed recovery (after 3 months) and patients who needed a second course of IV L‐AmB were included, the success rate was found to be 63% 13 . Lemieux et al, in the JD MacLean Center for Tropical Diseases at McGill University, reported that a 69% cure rate was found when IV L‐AmB was used as a first‐line agent for CL and 75% cure rate when IV L‐AmB was used as a first or second‐line agent 25 . In the study of Solomon et al, 13 patients with CL caused by L. tropica were treated with 6 doses of 3 mg/kg/day IV L‐AmB in the first 5 days and on the tenth day, a clinical improvement of 84% was reported, and the no recurrence was observed in the 11‐month follow‐up 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also consistent with previous observations, positive cases were associated with recent travel to Central and South America, particularly Costa Rica, where there is a high incidence of leishmaniasis (Table 1, Table S2) (12,28,29,31). 11.7% of cases in this work were in children younger than 10 and 6.4% in the 10-18 age range, adding to reports of pediatric infection in the U.S. (12,13,29,32,33) Migration-related leishmaniasis has increased globally, but U.S.-specific data has been limited to sporadic case studies (28,(34)(35)(36)(37). This work identifies 7 cases (7.4% of all positive) of likely migration-related infection originating from multiple continents, highlighting a need for increased clinician awareness in this vulnerable population (Table 1, Table S3).…”
Section: Discussionmentioning
confidence: 84%
“…[22][23][24] Factors like poverty, immune deficiencies, migration, gender inequality, and housing conditions significantly affect transmission and prevalence. [25][26][27][28][29][30][31][32][33][34][35] Deforestation further exacerbates the disease's spread by altering vector behavior and disease pattern a cross regions. 35 Further research is needed in Khyber Pakhtunkhwa to understand Cutaneous leishmaniasis prevalence and affected demographics for effective policy planning.…”
mentioning
confidence: 99%